Maghrebi women’s cinema. Gender, body and politics as subversive axes - Awatef Ketiti (Arte, Individuo y Sociedad)
Films by women directors constitute a revolutionary stylistic discourse on the cultural scene in the Maghreb. With their subversive filmography, these filmmakers have explored political, religious, and sexual taboos while forging a new visual style for self-expression. The aim of this study is to make a thematic analysis of the filmography of Maghrebi women directors and to shed light on the subversive features that characterise this aesthetic project. Two methods are used for this analysis: a compilation case study covering the history of this cinema; and an analysis of three films by three young Maghrebi directors of the new generation: Adam by Maryam Touzani (Morocco); As I Open My Eyes by Leyla Bouzid (Tunisia); and Papicha by Mounia Meddour (Algeria). The findings reveal a significant evolution in Maghrebi women’s cinema, culminating in a new approach to filmmaking that is highlighted in the works of young women filmmakers. Three key trends are clear: the centrality of women’s issues; the transgression of gender, political and religious taboos; and an emphasis on the body and on female desire.